Огляд сучасних методів мережної стеганографії - Щербак, А.; Дарраж Муад; Шаповал, М. (ХНУРЕ, 2020)
An object of study is a process of stenographic information hiding, which counteracts the threat of unauthorized access to it. A subject of the research is network steganography methods based on changes in header and data fields in protocols. An aim of the work is to research and implement network steganography methods, with special emphasis on consideration of quality assessment indicators of stenographic methods. Choose a method that could be used to improve the system of remote user authentication in communication channels by increasing the resistance to cracking and noise immunity of the system.